Motivation and learning strategies among students in upper secondary education: grade level differences and academic outcomes - Diseth, Åge (Frontiers in Education, 2025)
This study examined grade-level differences in motivation and learning strategies and their relations to academic achievement (GPA) from a self-regulated learning (SRL) perspective. Participants were 401 Norwegian upper secondary/senior high school students (mean age = 17.1) who completed a 27-item short-form MSLQ assessing intrinsic and extrinsic goal orientation, self-efficacy, and cognitive, metacognitive, and resource management strategies. Confirmatory factor analysis supported a nine-factor model. Configure, metric, and scalar invariance held across grades 1–3, enabling mean comparisons. ANOVAs indicated significant grade-level declines in intrinsic goals, organization, and effort management, with the largest differences between first- and third-year students. All motivation and strategy variables correlated positively with GPA, with self-efficacy showing the strongest association (r = 0.51). Hierarchical regression revealed that motivation explained 33% of GPA variance, with cognitive strategies adding 4% and metacognitive/resource strategies adding 5%, while self-efficacy remained as the strongest predictor (β = 0.38). Findings underscore the robustness of the abbreviated MSLQ, highlight declines in intrinsic motivation and effort management across grades, and emphasize self-efficacy, metacognitive regulation, and effort management as key targets for instructional support. Limitations include a single-school sample and cross sectional design.